Cyber-war :bthe anatomy of the global security threat - Richards, Julian (Palgrave pivot, 2014)
Cyber-War provides a critical assessment of current debates around the likelihood and impact of cyber warfare. Approaching the subject from a socio-political angle, it argues that destructive cyber war has not yet been seen, but could be a feature of future conflict